Mechanisms of Ash Generation at Basaltic Volcanoes: The Case of Mount Etna, Italy - Polacci, Margherita; Andronico, Daniele; de’ Michieli Vitturi, Mattia; Taddeucci, Jacopo; Cristaldi, Antonio (Frontiers in Earth Science, 2019)
Basaltic volcanism is the most widespread volcanic activity on Earth and planetary bodies. On Earth, eruptions can impact global and regional climate, and threaten populations living in their shadow, through a combination of ash, gas and lava. Ash emissions are a very typical manifestation of basaltic activity; however, despite their frequency of occurrence, a systematic investigation of basaltic ash sources is currently incomplete. Here, we revise four cases of ash emissions at Mount Etna linked with the most common style of eruptive activity at this volcano: lava fountains (4–5 September 2007), continuous Strombolian activity transitioning to pulsing lava fountaining (24 November 2006), isolated Strombolian explosions (8 April 2010), and continuous to pulsing ash explosions (last phase of 2001 eruption). By combining observations on the eruptive style, deposit features and ash characteristics, we propose three mechanisms of ash generation based on variations in the magma mass flow rate. We then present an analysis of magma residence time within the conduit for both cylindrical and dike geometry, and find that the proportion of tachylite magma residing in the conduit is very small compared to sideromelane, in agreement with observations of ash componentry for lava fountain episodes at Mount Etna. The results of this study are relevant to classify ash emission sources and improve hazard mitigation strategies at basaltic volcanoes where the explosive activity is similar to Mount Etna.